Causal attribution in individuals with subclinical and clinical autism spectrum disorder: An fMRI study. (3rd May 2016) - Kestemont, Jenny; Vandekerckhove, Marie; Bulnes, Luis Carlo; Matthys, Frieda; Van Overwalle, Frank
Abstract : This neuroimaging study compares brain activation during causal attribution to three different attribution loci (i.e., self, another person, and situation) across a typical population without ( N = 20) or with subclinical autism spectrum symptoms ( N = 18) and a clinical population with autism spectrum disorder (ASD; N = 11). While they underwent fMRI, all participants read short sentences describing positive and negative behaviors and thoughts of another person directed toward the participant (i.e., "you"). Participants were then asked to attribute these behaviors to themselves, the other person, or the situation. Behavioral measures revealed self-serving attributions (i.e., attributing positive events to the self, while attributing negative events externally from the self) in all three participant groups. Neural measures revealed a great deal of shared activation across the three attribution loci and across the three participant groups in the temporo-parietal junction, the posterior superior sulcus, and the precuneus. Comparison between groups revealed more widespread activation in both subclinical and clinical ASD participants, which may be indicative of the extraneural resources these participants invest to compensate their impairments.